Specimen preparation by ion beam slope cutting for characterization of ductile damage by scanning electron microscopy. Issue 4 (8th February 2016) - Besserer, Hans‐Bernward; Gerstein, Gregory; Maier, Hans Jürgen; Nürnberger, Florian
ABSTRACT: To investigate ductile damage in parts made by cold sheet‐bulk metal forming a suited specimen preparation is required to observe the microstructure and defects such as voids by electron microscopy. By means of ion beam slope cutting both a targeted material removal can be applied and mechanical or thermal influences during preparation avoided. In combination with scanning electron microscopy this method allows to examine voids in the submicron range and thus to analyze early stages of ductile damage. In addition, a relief structure is formed by the selectivity of the ion bombardment, which depends on grain orientation and microstructural defects. The formation of these relief structures is studied using scanning electron microscopy and electron backscatter diffraction and the use of this side effect to interpret the microstructural mechanisms of voids formation by plastic deformation is discussed. A comprehensive investigation of the suitability of ion beam milling to analyze ductile damage is given at the examples of a ferritic deep drawing steel and a dual phase steel. Microsc. Res. Tech. 79:321–327, 2016 . © 2016 Wiley Periodicals, Inc.